2013
DOI: 10.1136/emermed-2013-202671
|View full text |Cite
|
Sign up to set email alerts
|

Proper compression landmark and depth for cardiopulmonary resuscitation in patients with pectus excavatum: a study using CT

Abstract: The LH of the sternum is an appropriate chest compression landmark in PE patients to compress LV, although the centre of LV shows slightly leftward displacement. Since PE patients have sunken chest, a 3-4 cm may be the proper compression depth in the patients when considering the current compression guideline in normal subjects is 5-6 cm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…HI is defined as the ratio between transverse diameter of the chest and the shortest distance between the sternum and vertebrae [19]. The HI is measured at the deepest aspect of the thoracic curve, with a normal chest HI ratio calculated as 2 or less.…”
Section: Haller Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…HI is defined as the ratio between transverse diameter of the chest and the shortest distance between the sternum and vertebrae [19]. The HI is measured at the deepest aspect of the thoracic curve, with a normal chest HI ratio calculated as 2 or less.…”
Section: Haller Indexmentioning
confidence: 99%
“…Only a few published papers reported on selection criteria for determining the magnitude of dosimetric benefit the DIBH technique offers individual patients [8]. This is especially important for patients with unfavorable chest wall shape (i.e., variations of pectus excavatum or pectus carinatum) [18,19]. Furthermore, patient selection for the DIBH technique varies across the literature from consultation to post-planning evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…5 The authors showed that displacement of the heart to the left was significantly greater in PE patients, with mean difference of 11 mm compared with controls, and that the left ventricle was located in all PE patients at the level of lower half of the sternum; they suggested this landmark is appropriate for CPR in PE patients. They defined the external thickness of the chest as the distance between the anterior and posterior skin margin and the internal thickness as the distance between the posterior sternum and anterior vertebrae.…”
Section: Sirmentioning
confidence: 96%
“…Abnormal growth of the sternum and ribs results in a concave appearance of the anterior chest wall. The posteriorly depressed sternum compresses and displaces the heart and lungs 2‐5 . Patients with pectus excavatum frequently complain of cardiopulmonary symptoms such as dyspnea, tachycardia, and exercise intolerance 2 due to decreased pulmonary function 2,6 and cardiac abnormalities 4,6‐8 .…”
Section: Introductionmentioning
confidence: 99%
“…In a recent retrospective study, computed tomography was used to determine the optimal compression site and depth during CPR in adult patients with pectus excavatum 5 . The authors showed that the heart was displaced more leftward in patients with pectus excavatum than in the normal population (mean difference, 11 mm) but mentioned that the lower half of the sternum was the appropriate compression site for CPR.…”
Section: Introductionmentioning
confidence: 99%